First report of Taenia pisiformis Cysticercus infestation in Domestic rabbits in Hajjah city Yemen - Nabil M Mogalli (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
Cysticercus pisiformis is larval forms of Taenia pisiformis tapeworm. t has been observed in rabbits that are considered the intermediate host. In this study Cysticercus pisiformis was observed in domestic rabbits at routine necropsy examination. Cysticercus pisiformis was observed in 23 (76.7) out of 30 (23.3%) of domestic rabbits of both sexes was 2 months - 2 years old. the Parasites were observed only in July2018 and February 2020. After noticing the changes in the shape of the liver, which appeared in white to cream cysts were ranging from 3- 8 mm in diameter and varying in sizes, The aim of this study was to identify, which is the causative of these changes in the liver and the nature of cysts developing around the stomach and what organisms belong to them, as well as the preparation of tissue sections of the liver to study histopathological changes. Our results revealed, several cysts were found around the stomach and viscera. morphological form of these cysts depicted the presence of Cysticercus pisiformis of Taenia pisiformis and the larval stage was also seen moving near the diaphragm. Gross and histopathological examination revealed that liver was the most severely affected organ. Varying degrees of focal necrosis, hepatocellular degeneration, inflammation associated with viable and degenerated cysts were observed in the liver. Degenerated cysts revealed varying degrees of dystrophic calcification. Our results revealed, (23) were infected (76.6%) of Cysticercus pisiformis of adult parasite Taenia pisiformis it is the first report in Hajjah / Yemen.